Comparison of Bupivacaine (0.5%) and Bupivacaine (0.5%) with Dexmedetomide for Spinal Anesthesia in Lower Abdominal and Pelvic Surgery: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
Background: Dexmedetomiodine has also been used intrathecally to enhance the duration of motor and sensory blockade produced by hyperbaric bupivacaine. By increasing the dose of intrathecal dose of intrathecal dexmedetomidine it has been found that there is a significant increase in duration of motor and sensory blockade produced by intrathecal hyperbaric bupivacaine. Purpose of this study was to evaluate whether addition of dexmedetomidine changes the characteristics of bupivacaine 0.5% analgesia and other effects when injected intrathecally. Materials & Methods: This prospective, double-blind, randomized, controlled study was conducted in 100 patients of ASA PS I-II, aged between 20-60 yrs, of either sex, scheduled for elective lower abdominal and pelvic surgery were chosen and divided into two groups. Patients were randomly allocated to receive intrathecally either 3ml of 0.5% hyperbaric bupivacaine plus 1ml normal saline (group X) or 3ml of 0.5% hyperbaric bupivacaine plus dexmedetomidine 4 µg in 1 ml (group Y). The time taken to achieve peak sensory (T10 dermatome) and motor blockade (Bromage score 3), duration of block, recovery characteristics and hemodynamic changes were recorded. Any adverse symptoms like nausea, vomiting, shivering, pruritis, and sedation etc were noted.Results: The mean time of sensory block to reach T10 dermatome was 5.56±1.23 minutes in Group Y, 6.48±1.18 minutes in Group X.The mean time to reach Bromage 3 scale was 8.94±1.62 minutes in Group Y and 11.88±1.42 minutes in Group X. The regression time to Bromage 0 was 291.7±30.2 minutes for Group Y and 144.8 ±10.5 minutes for Group X. Onset and regression of sensory and motor block were highly significant ( p
Keywords: : Spinal anesthesia, lower abdominal surgery, pelvic surgery, bupivacaine, dexmedetomide, motor and sensory blockade